Total Quality Management and Service Quality on Customer Satisfaction in Public Services - Muhammad Aqsa; M. Risal; Raodlah Nur (PINISI Discretion Review, 2021)
The big problem faced by service providers is how customer satisfaction should be a top priority. Some of the determining factors in customer satisfaction are Total Quality Management and Service Quality. This study aims to determine the effect of Total Quality Management and Service Quality on Customer Satisfaction. With a sample of 76 respondents. By using multiple regression analysis. The results showed that Total Quality Management had a significant and positive effect on customer satisfaction. Likewise, service quality has a significant and positive effect on customer satisfaction. This significant effect applies either partially or simultaneously.